Optical Heisenberg Landau Lifshitz electromotive microscale - Körpınar, Talat; Körpınar, Zeliha (Springer, 2023)
In this paper, we define electrical Heisenberg synthetic-solitonic Landau LifshitzNLES electromotive phi(k(1)), phi(k(2)), phi(k(3)) microscales. Then, we construct Heisenberg Landau Lifshitz NLES electrical optimistic synthetic-solitonic phi(k(1)), phi(k(2)), phi(k(3)) density. Finally, we have electrical Heisenberg Landau Lifshitz synthetic-solitonic first type electric phi(k(1)), phi(k(2)), phi(k(3)) microscale.
Keywords: Optical Heisenberg NLES frame; Heisenberg Landau Lifshitz microscale; Synthetic-solitonic density; Heisenberg NLES electromotive microscale